Melt Flow during Silicon Crystal Growth - WATANABE, Masahito; HIBIYA, Taketoshi; KAKIMOTO, Koichi; EGUCHI, Minoru (Journal of Japan Society of Fluid Mechanics, 1994)
The quality of large semiconductor crystals grown from silicon melts is significantly affected by the heat and mass transfer in the melt. The characteristics of silicon flows are reviewed by focusing on the Coriolis force in the rotating melt. Description of flow instability is included that shows our level of understanding of melt convection with a low Prandtl number.